Acitretin - Nihal Kundakçı (Galenos Publishing House, 2022)
Acitretin is a synthetic retinoid and an active metabolite of etretinate. It shows its action in psoriasis treatment by suppressing proliferation and enhancing the differentiation of keratinocytes. It differs from other systemic anti-psoriatic agents in that it is not immunosuppressive or cytotoxic. It is used as a monotherapy or in combination with phototherapy in various clinical forms of psoriasis. Due to its teratogenicity, its use in women of reproductive age is not recommended unless there is no alternative. Studies of this drug show that acitretin monotherapy is less effective in plaque psoriasis than other conventional systemic therapies but is superior to them in generalized, palmoplantar, pustular, and hyperkeratotic variants.